(untitled) (Jagannath University Journal of Life and Earth Sciences, 2025)
This study examined the relationships of smartphone addiction, psychological distress, and self-efficacy among Bangladeshi adolescents. A cross-sectional survey design was used to collect data from 320 school-going adolescents (160 girls and 160 boys) aged from 13 to 17 years (M = 15.00, SD = 1.41) in Dhaka. Convenience sampling techniques was used. Bangla version of Smartphone Addiction Scale (SAS), the General Self-Efficacy Scale (GSES), and the General Health Questionnaire-12 (GHQ-12) scales were used to collect data from the respondents. Obtained data were analyzed by employing descriptive statistics, correlation, t-test, and mediation analysis by Hayes’ Process Macro with the help of SPSS 27 version. Results revealed that smartphone addiction was positively correlated with psychological distress (r = .86, p< .01) and negatively correlated with self-efficacy (r = –.88, p< .01). Psychological distress was also negatively correlated with self-efficacy (r = –.84, p< .01). No significant gender differences were found in smartphone addiction, self-efficacy, and psychological distress. Mediation analysis indicated that psychological distress partially mediated the relationship between smartphone addiction and self-efficacy. These findings suggested that increased smartphone use may elevate psychological distress and diminish adolescents self-efficacy. The results highlight the importance of early interventions aimed at managing smartphone use and improving adolescents’ mental health and self-efficacy. Jagannath University Journal of Life and Earth Sciences, 10 (2): 143-152 (June 2024)